Search for direct pair production of scalar top quarks in the single- and dilepton channels in proton-proton collisions at ?s= 8 TeV - The, C. M. S. collaboration; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; et al. (My University, 2016)
Results: are reported from a search for the top squark t ˜ 1, the lighter of the two supersymmetric partners of the top quark. The data sample corresponds to 19.7 fb?1 of proton-proton collisions at s=8 TeV collected with the CMS detector at the LHC. The search targets t˜1?b?˜1± and t˜1?t(?)?˜10 decay modes, where ?˜1± and ?˜10 are the lightest chargino and neutralino, respectively. The reconstructed final state consists of jets, b jets, missing transverse energy, and either one or two leptons. Leading backgrounds are determined from data. No significant excess in data is observed above the expectation from standard model processes. The results exclude a region of the two-dimensional plane of possible t ˜ 1 and ?˜10 masses. The highest excluded t ˜ 1 and ?˜10 masses are about 700 GeV and 250 GeV, respectively.[Figure not available: see fulltext.] © 2016, The Author(s).
Citation: The, C. M. S. c., Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., . . . Woods, N. (2016). Search for direct pair production of scalar top quarks in the single- and dilepton channels in proton-proton collisions at ?s= 8 TeV. Journal of High Energy Physics, 2016(7). doi:10.1007/JHEP07(2016)027
Keywords: Hadron-Hadron Scattering (Experiments); Supersymmetry; Top Squark